Executive's guide to cloud computing - Marks, Eric A.; Lozano, Bob (Hoboken, N.J. : Wiley, 2010)
This book explains what cloud computing is to the busy C-level executive from an introduction to strategic implications for a corporation.
Includes bibliographical references and index.
oif 22/06/15
Loan
Keywords: Business enterprises - computer network; Information technology - management; Cloud computing